TAMBUSAI VISION: FILM SEJARAH BERBASIS ARTIFICIAL INTELLIGENCE TENTANG PERLAWANAN TUANKU TAMBUSAI SEBAGAI INOVASI PEMBELAJARAN SEJARAH LOKAL DI ERA SOCIETY 5.0 - Lubis, Dhea Annisa (Jurnal Pendidikan Sejarah Indonesia, 2025)
The development of technology in the era of society 5.0 has given rise to new innovations in the form of advanced technology, one of which is artificial intelligence (AI). The presence of Artificial Intelligence makes it easier to assist human tasks in various activities, including the world of education. In this case, education is required to adapt learning needs to the development of the times. Therefore, the use of Artificial Intelligence in learning, especially local history learning, is an opportunity to improve the quality of learning to be more optimal. The purpose of this study is to develop media in local history learning, namely an Artificial Intelligence-based historical film about the resistance of Tuanku Tambusai and encourage the use of technology as a learning innovation in line with the 5.0 era. This study uses the 4D model (Define, Design, Develop, Disseminate). The research subjects were 36 students in class XI 3 of SMAN 19 Pekanbaru. The data sources were obtained from interviews and questionnaires. This study used qualitative descriptive techniques to analyze interview information and quantitative analysis techniques to process the data in the questionnaire. Validation carried out showed that the assessment from material experts reached 85%, while from media experts obtained 95%. These results confirm that both are in the very feasible category. In the pilot phase, the small group scored 84%, while the large group achieved 95%, and both were rated in the same category: very appropriate. Therefore, this AI-based historical film is suitable for implementation in schools. AI-based historical films can help students develop a better understanding of history through meaningful and visual learning experiences and foster pride in the struggles of local figures, particularly Tuanku Tambusai.